Different components of air pollutants and neurological disorders - Fu, Chunlia; Kuang, Daibing; Zhang, He; Ren, Jinxin; Chen, Jialong (Frontiers in Public Health, 2022)
As we all know, the harmful effects of air pollution can cause various diseases. Most research on the hazards of air pollution focuses on lung and cardiovascular diseases. In contrast, the impact of air pollution on the central nervous system (CNS) is not widely recognized. Air pollution can cause various neurological diseases such as nervous system inflammation, neurodegeneration and cerebrovascular barrier disorder, but the different components of air pollutants leading to neurological diseases is still a controversial issue. This work summarizes the effects of air pollutants of different components, including particulate matter, ozone, sulfur oxides, carbon oxides, nitrogen oxides and heavy metals, on the nervous system and describes the impact of various air pollutants on neurological disorders, which provides ideas for follow-up research.